Feasibility Assessment of A Nursing Learning E-Book Through Content and Media Expert Validation - Hingmane, Gusti Omkang; Rahmadonna, Sisca (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to evaluate the feasibility of using an e-book as a learning medium for students in the Nursing Vocational High School (SMK) program through validation by content and media experts. The research employed a descriptive quantitative method with a validation approach. Validation by content experts included assessments of content substance, language use, and material presentation structure, while validation by media experts assessed visual design, readability, and technical aspects of the e-book. Data were analyzed using a feasibility percentage formula. The validation results showed that the content expert assessment yielded a feasibility score of 60% (moderately good), while the media expert assessment reached 80% (good). Therefore, the e-book is deemed feasible for educational use with several recommended improvements. The novelty of this research lies in its application of a user-centered design approach, which is still rarely implemented within the context of vocational nursing education in Indonesia. Therefore, this thoroughly validated e-book may serve as a valuable reference for the development of effective and high-quality digital learning media in vocational education.